Dampak Kegiatan Pariwisata di Pantai Indrayanti terhadap Ekonomi Masyarakat Sekitar - , SAPTO WULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gunungkidul Regency has been known by an arid region, but behind the condition Gunungkidul has many interesting tourism attractions, one of them is Indrayanti Beach, Indrayanti Beach is a beach that has just evolved and being popular in Gunungkidul. Indrayanti beach is located in Tepus Village, Tepus Sub-district who had known the chronic shortage of watersupply when the dry season arrives and the resulted of agricultural sector which is the principal livelihood of the population become not productive, but since Indrayanti Beach into a bustling attraction and visited by tourists has given changes in economic activity to local communities, those activities have a positive impact to the local economy such as the emergence of businesses established by the local community and employment for local communities. This study aims to reveal the economic impact of tourism activities in Indrayanti Beach to local communities, using interviews method to anyone type of business owners and workers in Indrayanti Beach and analyzes to be qualitative descriptive analysis. From the results of this study revealed that tourism activity in Indrayanti Beach thas encouraged the local community to build various types of businesses, including:culinary business, services business, souvenirs/merchandise business and employment opportunities for local communities, revenue from the economic activity in the Indrayanti Beach can give contribution to economic life as a supplemental income even many who do make it as basic livelihood.